Market analysis for cultured proteins in low- and lower-middle income countries. - Herrick, T.; Gannon, S.; Kreis, Katharine; Zobrist, S.; Harner-Jay, Claudia; Goldstein, J.; Mason, S.; Olander, L.; Pérez, N.; Ringler, Claudia; Shindell, D.; Parker, M. E. (PATH, 2019)
The global burden of malnutrition is unacceptably high.10 Worldwide, an estimated 22% of children under the age of five were stunted and 8% were wasted in 2018.11 Low-quality diets lacking in essential vitamins, minerals, proteins, and other nutrients are a key contributor to this burden.12 Animal-source foods—such as meat, poultry, fish, eggs, and dairy—are important components of a diverse diet and provide high-quality proteins and other essential nutrients that promote optimal growth and development.13,14,15,16,17As populations and incomes grow, the global demand for animal-source foods is projected to increase substantially, particularly in many low- and lower-middle income countries (LMICs).18,19 However, cost is currently a significant barrier to animal-source food consumption. In addition, meeting this growing demand for animal-source foods will require rapid increases in livestock production, which has significant environmental impacts, requiring considerable land, water, chemical, and energy inputs.10,17,18 Global food production is responsible for roughly one-quarter of all greenhouse gas emissions, most of which (up to 80%) are related to livestock.20,21 Livestock production is also a contributor to water pollution, deforestation, land degradation, overfishing, and antimicrobial resistance.20,22,23 Given these challenges, this report aims to assess the market for potentially more sustainable alternative proteins and their potential for use in LMIC settings. The report focuses on proteins derived from fermentation-based cellular agriculture, called cultured proteins, given their potential near-term time to market and their potential impact in LMIC populations. Most cultured protein manufacturers are developing proteins that are present in animal-source milk and eggs.